Effects of Natural Convection from an Open Square Cavity Containing a Heated Circular Cylinder (Bangladesh Journal of Scientific and Industrial Research, 2012)
The problem of natural convection heat transfer in a square open cavity containing a heated and conducting circular cylinder at the centre is analyzed in this paper. As boundary conditions of the cavity, the left vertical wall is kept at a constant heat flux, bottom and top wall are kept at different high and low temperature respectively. The remaining side is open. Two dimensional laminar steady state natural convection is considered. This configuration is related in the design of electronic devices, solar energy receivers, uncovered flat plate solar collectors geothermal reservoirs etc. The fluid is concerned with different Prandtl numbers, Grashof numbers and the properties of the fluid are assumed to be constant. The development of Mathematical model is governed by the coupled equations of continuity, momentum and energy and is solved by employing Galerkin weighted finite element method. Flow field and heat transfer were predicted for fluid with Pr = 0.72 , 1.0 ,7.0; Gr = 103, 104, 105 ,106; inclination angles of the cavity are ? = 0°, 15°, 30°, 45° and diameter ratio dr = 0.2.The average Nusselt number increases as the increases of inclination angle of the cavity for lower Pr and lower temperature at bottom wall. The average Nu increases mainly for higher inclinations and for higher Gr. Various vortices and recirculations are formed into the flow field for higher Pr and higher temperature at the bottom wall. DOI: http://dx.doi.org/10.3329/bjsir.v47i1.10718Bangladesh J. Sci. Ind. Res. 47(1), 19-28, 2012